Snort 2.1 intrusion detection - Beale, Jay.; Alder, Raven (Rockland, MA : Syngress, 2004)
Called "the leader in the Snort IDS book arms race" by Richard Bejtlich, top Amazon reviewer, this brand-new edition of the best-selling Snort book covers all the latest features of a major upgrade to the product and includes a bonus DVD with Snort 2.1 and other utilities. Written by the same lead engineers of the Snort Development team, this will be the first book available on the major upgrade from Snort 2 to Snort 2.1 (in this community, major upgrades are noted by .x and not by full number upgrades as in 2.0 to 3.0). Readers will be given invaluable insight into the code base of Snort, and in depth tutorials of complex installation, configuration, and troubleshooting scenarios. Snort has three primary uses: as a straight packet sniffer, a packet logger, or as a full-blown network intrusion detection system. It can perform protocol analysis, content searching/matching and can be used to detect a variety of attacks and probes. Snort uses a flexible rules language to describe traffic that it should collect or pass, a detection engine that utilizes a modular plug-in architecture, and a real-time alerting capability. A CD containing the latest version of Snort as well as other up-to-date Open Source security utilities will accompany the book. Snort is a powerful Network Intrusion Detection System that can provide enterprise wide sensors to protect your computer assets from both internal and external attack. * Completly updated and comprehensive coverage of snort 2.1 * Includes free CD with all the latest popular plug-ins * Provides step-by-step instruction for installing, configuring and troubleshooting.
Ch. 1. Intrusion detection systems -- Ch. 2. Introducing Snort 2.1 -- Ch. 3. Installing Snort -- Ch. 4. Inner workings -- Ch. 5. Playing by the rules -- Ch. 6. Preprocessors -- Ch. 7. Implementing Snort output plug-ins -- Ch. 8. Dealing with the data -- Ch. 9. Keeping everything up to date -- Ch. 10. Optimizing Snort -- Ch. 11. Mucking around with barnyard -- Ch. 12. Active response -- Ch. 13. Advanced Snort
Includes index.
Keywords: Computer networks -- Security measures; Computer security; Electronic books